How to study as a mathematics major - Alcock, Lara, ....- (Oxford : Oxford University Press, 2013)
> Explores how to engage with the academic content of a mathematics major in the USA and territories/institutions with a US-style educational setup > Also covers aspects of university life separate from mathematics > Designed to help students to recognize and reflect on their own experiences and to anticipate, articulate and overcome the challenges they encounter > Unique subject-specific study guide for mathematics students. Every year, thousands of students in the USA declare mathematics as their major. Many are extremely intelligent and hardworking. However, even the best will encounter challenges, because upper-level mathematics involves not only independent study and learning from lectures, but also a fundamental shift from calculation to proof. This shift is demanding but it need not be mysterious — research has revealed many insights into the mathematical thinking required, and this book translates these into practical advice for a student audience. It covers every aspect of studying as a mathematics major, from tackling abstract intellectual challenges to interacting with professors and making good use of study time. As the first mathematics-specific study guide, this friendly, practical text is essential reading for any mathematics major. Readership: Students in their Sophomore year looking to make the transition from their broad subject base to majoring in mathematics; First year mathematics majors struggling on their course; Mathematics lecturers to better understand the difficulties encountered by their students
Part 1 discusses the nature of upper-level mathematics, and explains how students can adapt and extend their existing skills in order to develop good understanding. Part 2 covers study skills as these relate to mathematics, and suggests practical approaches to learning effectively while enjoying undergraduate life.
Includes bibliographical references (pages 248-262) and index.
Keywords: Mathematics -- Study and teaching (Higher).; Studievaardigheden; Study skills; Wiskunde -- Hoger onderwijs